Turkey's relations with the Middle East : How does the competition with Iran affect Turkey's relations with Syria and Iraq? - Kaşıkara, Ali; Weinfurter, Jaroslav; Rolenc, Jan Martin, 1980-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
This thesis seeks to examine Turkey's foreign policy toward Syria and Iraq, with a focus on how its strategies are shaped by its competition with Iran within the broader Middle East. The research will demonstrate that Turkey and Iran have been historical rivals. This long-standing rivalry has had significant repercussions across the Middle East, occasionally bringing the two nations to the brink of conflict. Both Turkey and Iran have consistently sought to expand their influence within the region, engaging in a continuous struggle for regional dominance. The thesis aims to study how this dynamic continues to shape foreign policy decisions and regional security dynamics in the Middle East today.
Vedoucí práce: Jaroslav Weinfurter
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses